Optical Modeling of Microcrystalline Silicon Deposited by Plasma-Enhanced Chemical Vapor Deposition on Low-Cost Iron-Nickel Substrates for Photovoltaic Applications. (2016) - Mrázková, Z.; Postava, K.; Torres-Rios, A.; Foldyna, M.; i Cabarrocas, P. Roca; Pištora, J.
Abstract: This paper deals with the optical modeling of thin hydrogenated microcrystalline silicon films grown on flexible low-cost iron-nickel alloy substrates by low-temperature (175 °C) plasma-enhanced chemical vapor deposition. This material serves as the absorber in solar cells and hence it has direct impact on the resulting solar cell performance. Since the crystallinity and the material quality of hydrogenated microcrystalline silicon films evolve during the growth, the deposited film is inhomogeneous, with a rather complex structure. Real-time spectroscopic ellipsometry has been used to trace the changing composition of the films. In-situ ellipsometric data taken for photon energies from 2.8 to 4.5 eV every 50 seconds enabled us to study the evolution of the monocrystalline silicon fraction of the hydrogenated microcrystalline silicon films.